Consensus opinion on the management of patients with neuromyelitis optica spectrum diseases: issues of terminology and therapy - V. S. Krasnov; K. Z. Bakhtiyarova; E. P. Evdoshenko; D. S. Korobko; T. O. Simaniv; N. A. Totolyan; N. V. Khachanova; M. V. Shumilina; M. V. Davydovskaya (Неврология, нейропсихиатрия, психосоматика)
Neuromyelitis optica spectrum disorders (NMOSD) are a group of inflammatory diseases of the central nervous system characterized by episodes of immune-mediated astrocytopathy, inflammatory demyelination and axonal damage, predominantly affecting the optic nerves and spinal cord. Currently, there are several unresolved issues that make it difficult to provide medical care to patients with NMOSD. The objective of this publication is to present the results of the work of the Russian experts panel, held in September 2022. The consensus council of experts adopted the main definitions and terms for NMOSD, proposed a therapeutic algorithm to prevent exacerbations in patients with NMOSD with serum IgG antibodies to aquaporin-4 (AQP4-IgG).The experts formulated profiles of patients with NMOSD to whom eculizumab may be recommended, and proposed a risk management plan during the treatment with this drug. The experts worked out the next steps, which are necessary for the improvement of medical care for these patients: development of unified electronic register of patients with NMOSD in the Russian Federation, development and approval of clinical guidelines.